Assistance of Community Cadres for Improving Mental Health in Bandarharjo Village - Betie Febriana; Dwi Heppy Rochmawati; Wahyu Endang Setyowati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
People with Mental Disorders (ODGJ) is someone who experiences mental disorders and needs appropriate and immediate treatment. Currently, the handling of ODGJ has not been carried out properly and appropriately. The cause of the lack of proper management of ODGJ in society is due to a lack of knowledge about the role of family, community/religious leaders and mental health cadres (KKJ). In this year's community service program, we provide promotions and health education to KKJ about the role and management of ODGJ. This activity was attended by 14 KKJ people consisting of RW 4 and 8. This program provided material related to ODGJ to the role of a KKJ, after being given the material the cadres were given the opportunity to practice with fellow cadres in carrying out the ODGJ approach. After being given material and training, the KKJ were able to review the program that had been provided.